Management's perceptions of factors that influence firm performance : Chinese international subsidiaries in South Africa - Ren, Hongyan (My University, 2014)
Firm performance and its determinants in emerging markets have generated much attention in recent years. This study examined the perceived performance of Chinese international subsidiaries in South Africa and the influence of four factors, namely, host country institutions, financial capital, human resource management, and entrepreneurial orientation. Questionnaires were distributed to 46 Chinese subsidiaries operating in South Africa. The analysis of the results used the Spearman's rho to test the relationship of the four factors with the performance of the Chinese subsidiaries. The findings showed a positive relationship between entrepreneurial orientation and perceived performance of Chinese international subsidiaries. A negative relationship was revealed between sufficient initial capital investment and the perceived performance of Chinese international subsidiaries. The remaining two factors did not show any significant influence on the perceived performance of Chinese international subsidiaries. This study provided empirical evidence to support the existing performance theories in the context of emerging economies. This research examines the performance of Chinese foreign direct investment in South Africa. Both countries involved are developing countries, which in itself was an unusual research setting. Furthermore, this paper could provide guidance for those Chinese international companies that are already operating, or are about to set up business, in South Africa. The findings of this research indicated that Chinese international subsidiaries could adopt EO as a firm strategy to improve performance. The South African government could help firms to achieve better performance by creating a social climate to encourage innovation, protect innovative products and develop its institutions to give every firm fair access to information that is key when predicting market trends.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.